BLENDED-LEARNING USING THE GLOBAL HEALTH NETWORK ONLINE RESOURCES: A PILOT STUDY. (12th February 2017) - Allen, Elizabeth; Leisegang, Cordelia; Furtado, Tamzin; Loggerenberg, François Van; Lang, Trudie
Abstract : Background: Enhancing The Global Health Network's online offerings (TGHN eLearning, www.theglobalhealthnetwork. org) through local facilitation of its outputs may enable its uptake by clinical research staff. To explore this issue, we aimed to design and pilot a blended-learning programme in collaboration with South African research team members. Methods: A participatory research design was used, with purposively-selected support staff and their line managers. Formative semi-structured interviews with the former and focus group discussions with the latter sought reflection on current learning opportunities and career development experiences and needs. Staff then helped design and pilot a practical, feasible blended-learning programme over an approximately 6-month period. The pilot was assessed on reflections of its value that were elicited in follow-up discussions with participants. Results: Forty-five clinical research field workers, nurses, co-ordinators, data managers and laboratory personnel (and their respective line managers) took part. Formative discussions suggested staff generally had the necessary skills for their jobs, however they often lacked time and finances to develop a career path. The blended-learning menu of options for staff that they then co-designed and piloted included: facilitated one-to-one or group TGHN eLearning sessions followed by a discussion forum hosted by a volunteer content-expert; job shadows; guidance in accessing training opportunities/ resources; twinning with other research groups or staff; and a skills-sharing workshop. Feedback on their experience of the programme was very positive from those who got 'hooked', particularly as regards the non-threatening learning environment, building of IT competence and networking opportunities. However, staff's personal time constraints, and our challenges in supporting remote teams, were evident for some despite the pragmatic design. Conclusions: This flexible, practical and feasible blended-learning program catalysed the self-development of many research staff in the pilot, and supported their busy line managers. As some challenges remain, the programme may require further modification when implemented in different contexts.